2021
DOI: 10.1007/s10681-021-02776-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and response to selection for storage root dry matter and associated traits in a population of yam bean (Pachyrhizus spp.) interspecies crosses

Abstract: The goal of yam bean improvement in Africa is to develop superior high yielding and high dry matter cultivars that are preferred for adoption. In this study, the estimates of variance components, heritability and response to selection were studied in F3 yam bean families selected from interspecies crosses targeting improvement of storage root dry matter and associated traits. Breeding populations were generated using North Carolina II (NC II) mating design involving high dry matter P. tuberosus chuin cultivar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The cost effectiveness of the RAD-Seq over other NGS based methods cannot be overemphasized as the use of restriction enzymes coupled with barcoding increases the efficiency of multiplexing allowing the genotyping of multiple or different populations at the same time [ 27 ]. In terms of breeding purposes and targeting the African continent, high dry matter content and associated traits has been defined as key traits [ 28 ] which greatly depends on the genetic background of AYB [ 29 ]. Higher contents of dry matter in AYB tubers would increase competitivity and adoption against other root and tuber crops especially cassava and yam.…”
Section: Introductionmentioning
confidence: 99%
“…The cost effectiveness of the RAD-Seq over other NGS based methods cannot be overemphasized as the use of restriction enzymes coupled with barcoding increases the efficiency of multiplexing allowing the genotyping of multiple or different populations at the same time [ 27 ]. In terms of breeding purposes and targeting the African continent, high dry matter content and associated traits has been defined as key traits [ 28 ] which greatly depends on the genetic background of AYB [ 29 ]. Higher contents of dry matter in AYB tubers would increase competitivity and adoption against other root and tuber crops especially cassava and yam.…”
Section: Introductionmentioning
confidence: 99%
“…In general, plant breeding programs have marked success in their genetic variability and in selecting progenitors that offer an excellent genetic combination for the different traits of agronomic interest (Agaba et al 2021). In this sense, this research demonstrated the precise selection of female parents in oil palm, with good genetic combinations in their progenies and high values of genetic gain in different traits of interest for world palm cultivation.…”
Section: Discussionmentioning
confidence: 72%
“…However, the use of morphological parameters alone could result in over-or underestimation of the degree of relatedness among cultivars. Therefore, the use of a genomic approach for determining relatedness among available accessions is needed because this approach will enhance the understanding of accessions before e cient hybridization across germplasms occurs (Agaba et al 2021). Understanding the genetic diversity of different accessions of Musa species harboring diverse genomic constitutions can improve the e ciency of banana and plantain breeding programs.…”
Section: Introductionmentioning
confidence: 99%